Developing a framework for housing financing: a case study of Nigeria’s sustainable low-cost housing via soft system methodology - Ebekozien, Andrew; Aigbavboa, Clinton Ohis; Samsurijan, Mohamad Shaharudin; Muhammad, Ahmad Kabir; Akinradewo, Opeoluwa (Engineering, construction, and architectural management, 2025)
PurposeSeveral governments in developing countries have attempted via policies and programmes to improve access to low-cost housing (LCH) finance for low-income house owners, but sustainability has been an issue. Therefore, sustainable LCH (SLCH) financing framework may mitigate issues hindering LCH financing sustainability in developing countries. There is a paucity of studies about SLCH financing through a framework in Nigeria. Thus, the study investigated the barriers facing low-income earners (LInEs) accessing SLCH finance and developed a framework for promoting Nigerian SLCH financing.Design/methodology/approachThe research employed a soft system methodology (SSM) to understand Nigeria’s LCH financing sustainability. The adopted method permitted a substitute to enhance LCH financing sustainability part way through a developed framework. The study conducted interviews across seven cities in Nigeria with selected practitioners.FindingsThe results were presented using the SSM seven steps. Findings reveal the state and barriers facing LInEs in accessing SLCH finance. Also, findings show that there is a need for a finance framework. It would improve sustainability, especially for intending low-income house owners across Nigeria’s cities. Findings include a framework to reposition LCH financing sustainability to promote homeowners for intending low-income house owners across Nigeria’s cities.Originality/valueBesides the developed LCH financing sustainable framework, housing policymakers and developers can employ SLCH financing to improve low-income intending house owners in Nigeria. This may be the first study to develop a SLCH financing framework using SSM in a developing economy.